CURRENT TRENDS IN MANAGEMENT PSYCHOLOGY IN INTERNATIONAL COMPANIES - Малюкіна, Анастасія (SWorldJournal, 2025)
In the context of globalization and rapid market changes, international companies face the necessity of implementing effective management methods that take into account the psychological aspects of their activities. The psychology of managerial activity h